Emergence and Return Times in a Colonial, Cave‐Dwelling Bat: Age and Sex Differences Driven by Reproductive Cycle - Nicola J. Bail; Lindy F. Lumsden; Terry Reardon; Emmi vanHarten; Paul Clissold; Thomas A. A. Prowse (Ecology and Evolution)
ABSTRACT The time that bats emerge and subsequently return from a colonial roost determines their maximum foraging period and influences their exposure to mortality risks. The order in which different age and sex cohorts emerge and return reflects variation in these cohorts' resource requirements. The critically endangered Southern Bent‐wing Bat (Miniopterus orianae bassanii) is an Australian insectivorous cave‐roosting colonial bat. Resource limitation is hypothesised to have contributed to its decline but may not affect all cohorts equally. We tagged and monitored 3462 wild Southern Bent‐wing Bats over 7 years with Passive Integrated Transponder technology. To infer resource requirements of different cohorts over the reproductive cycle, we estimated cohort‐specific peak emergence and return times and the frequency of nocturnal returns to the roost. The emergence and return behaviour varied with age, sex, and throughout the annual reproductive cycle. Although adult females and males behaved similarly during the non‐breeding period (winter), females emerged significantly (12–21 min) earlier and returned (27–62 min) later than males during pregnancy, lactation and weaning. Adult females were less likely than males to be detected overnight in the maternity roost while dependent young were present, suggesting that females prioritised maximising foraging over nocturnal nursing. When juveniles commenced flying, they delayed emergence until several hours after sunset (well after adults had departed the roost). During the 40‐day weaning period, they progressively emerged earlier, such that by the end of this period they emerged with the adults, then subsequently foraged for longer than adults over winter. Passive monitoring of emergence and return behaviour in colonial bats can provide valuable data to infer cohort‐specific resource requirements. Regular monitoring of a population's emergence and return times potentially allows for the early detection of changes in a resource requirements, and the use of PIT technology allows for the most vulnerable cohort(s) to be identified.